Lesbian Community and Activism in Britain 1940s–1970s: An Interview with Cynthia Reid. Issue 4 (21st March 2023) - Hubbard, Katherine A.
ABSTRACT: In this article, I provide a micro(oral)history of Cynthia Reid, one of only five women who founded the Minorities Research group—the first known lesbian organization in Britain, in 1963. Such activism paved the way for further lesbian liberatory action and the group did a great deal to combat the isolation experienced by many queer women across the country. They provided social opportunities as well as advice, and made more public calls for greater social acceptance. The group has been central to the interests of 20th-century queer historians, especially as the Minorities Research Group also produced the first lesbian magazine in Britain Arena Three . As a microhistory Cynthia's story informs many threads within queer history, including conceptualizations of masculinities, community, and change; while also challenging dominant notions that families and medical professionals were consistently unsupportive of queer people in the 1940s–1970s. In doing so, this article amplifies Cynthia's story in a way that means not only does it contribute nuance as a micro(oral)history to the broader field of queer scholarship but it also acts as a resource to stimulate further research.